Orientasi Kewirausahaan terhadap Kinerja Bisnis UMKM Kampung Wisata Kreatif Cibaduyut - Pamela Felita Fuad; Jurry Hatammimi (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the influence of entrepreneurial orientation on business performance in Micro, Small and Medium Enterprises (MSMEs) in the Cibaduyut Creative Tourism Village. A descriptive quantitative approach was used to analyze 385 MSMEs in the footwear industry sector using purposive sampling techniques. Data was collected through distributing questionnaires using Google Form. The hypothesis was tested using Structural Equation Modeling - Partial Least Squares (SEM-PLS) via SmartPLS software. Data analysis includes construct validity, reliability, and bootstrapping analysis to test statistical significance. The research results show that the dimensions of innovativeness, risk taking, proactiveness, autonomy and competitive aggressiveness significantly influence the business performance of MSMEs in the Cibaduyut Creative Tourism Village. In conclusion, these findings provide valuable insight for stakeholders in improving MSME business performance, especially in the Cibaduyut Creative Tourism Village environment. Keywords: Entrepreneurial Orientation, Business Performance, Creative Tourism Village